Micro-tuber production behaviour of some commercially important potato (Solanum tuberosum) cultivars - SHARMA, ASHWANI KUMAR; VENKATASALAM, E P; SINGH, R K (The Indian Journal of Agricultural Sciences, 2011)
Micro-tuber production behaviour of six commercially important cultivars of potato (Solanum tuberosum L.) was studied under standard medium and culture conditions using ten double node cuttings per flask. Significant differences were observed among the different potato genotypes for most of the characters during in vitro tuberization. Per cent micro-tuberization and number of stolons per nodal cutting were found to be maximum in Kufri Badshah and minimum in Kufri Pukhraj. Shoots weight/flask was maximum in Kufri Anand, followed by Kufri Badshah and Kufri Pukhraj, whereas, roots weight was higher in Kufri Badshah and minimum in Kufri Surya. The number of micro-tubers/flask was maximum (14.0) in Kufri Anand, which was almost same and statistically at par with three other varieties, viz Kufri Badshah, Kufri Bahar and Kufri Chipsona 1. Micro-tubers were found to be minimum in Kufri Pukhraj (7.5 tubers/flask). Total yield of micro-tubers/flask and harvest index were also maximum in Kufri Anand (3.7g and 0.29 respectively). Average weight of micro-tubers was maximum (0.27g) in Kufri Anand, whereas, tubers were of lighter weight in Kufri Surya (0.114g). The dry matter content of freshly harvested micro-tubers was maximum in Kufri Chipsona 1(19.65%) and minimum in Kufri Anand (14.75%). The proportions of normal shaped micro-tubers were significantly higher in Kufri Badshah (99%), at par with Kufri Chipsona 1, Kufri Bahar, Kufri Anand and minimum in Kufri Pukhraj (79.2%). The proportion of micro-tubers with burst lenticels was maximum in Kufri Pukhraj (43.5%) and minimum in Kufri Badshah (0.2%).